Integrated gene network analysis sheds light on understanding the progression of Osteosarcoma - Dey, Hrituraj; Vasudevan, Karthick; Doss C., George Priya; Kumar, S. Udhaya; El Allali, Achraf; Alsamman, Alsamman M.; Zayed, Hatem (Frontiers in Medicine, 2023)
Osteosarcoma is a rare disorder among cancers but the most common among sarcomas in children and adolescents. It has been reported to relapse and to be associated with side effects that hinder the development of an effective treatment plan. This study focused on understanding the underlying mechanism of Osteosarcoma using gene interaction network analysis. Gene interaction network provides a comprehensive overview of functional gene analysis by providing insight into how genes cooperatively interact to elicit a response. It is a dynamic framework that provides a clear understanding of biological complexity and a pathway from the gene level to interaction networks. We identified the potential hub genes and their functional partners using gene interaction network analysis. Our study revealed that the hub genes viz.TP53, CCND1, CDK4, STAT3, and VEGFA have the highest number of interactions and have a high cluster density. Their involvement in key signaling pathways, such as the FOXM1 transcription factor network, FAK-mediated signaling events, and the ATM pathway, makes them potential candidates for drug development.